Extensive marine-terminating ice sheets in Europe from 2.5 million years ago - Rea, Brice R. (Sci Adv, 2018)
Geometries of Early Pleistocene [2.58 to 0.78 million years (Ma) ago] ice sheets in northwest Europe are poorly constrained but are required to improve our understanding of past ocean-atmosphere-cryosphere coupling. Ice sheets are believed to have changed in their response to orbital forcing, becoming, from about 1.2 Ma ago, volumetrically larger and longer-lived. We present a multiproxy data set for the North Sea, extending to over a kilometer below the present-day seafloor, which demonstrates spatially extensive glaciation of the basin from the earliest Pleistocene. Ice sheets repeatedly entered the North Sea, south of 60°N, in water depths of up to ~250 m from 2.53 Ma ago and subsequently grounded in the center of the basin, in deeper water, from 1.87 Ma ago. Despite lower global ice volumes, these ice sheets were near comparable in spatial extent to those of the Middle and Late Pleistocene but possibly thinner and moving over slippery (low basal resistance) beds.